Hydroxyapatite – barium/strontium titanate composite coatings for better mechanical, corrosion and biological performance. (2021) - Senthilkumar, G.; Kaliaraj, Gobi Saravanan; Vignesh, P.; Vishwak, R. Sudharshan; Joy, T. Nivin; Hemanandh, J.
Abstract: The effect of piezoalectricity from piezoelectric materials promotes the growth of bone. However, the material should be subjected to stress before it can produce an electric charge that promotes repair of bones and reconstruction of it conducive to healing of fracture. This mainly includes the coatings, hardness, tribometer and biological tests on the composite material. Initially the widely used stainless steel metal of 316L grade is selected and then it was cut into small samples of specific dimensions 10 mm × 10 mm × 4.5 mm and 20 mm × 10 mm × 4.5 mm. Then BaTiO3 (Barium titanate) doped hydroxyapatite (HA) and SrTiO3 (Strontium titanate) doped HA powders were coated on the stainless steel samples by Plasma Spray Technique. X Ray Diffraction was done to characterise the material. Vickers hardness test was performed to check the hardness of various coated samples. Then tribology was performed using linear reciprocating test to examine the wear resistance of the coated sample. The effect of piezoelectricity of BaTiO3 and SrTiO3 promoted the growth of osteoblasts and interaction with HA, which was better than the piezoelectric effect of HA alone. The result show that BaTiO3 doped hydroxyapatite and SrTiO3 doped hydroxyapatite coatings could enhance the bio mineralization (calcium precipitation) process.